2016
DOI: 10.1128/aem.00789-16
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Responses of the Interactions between Clostridium cellulovorans 743B and Rhodopseudomonas palustris CGA009 in a Cellulose-Grown Coculture for Enhanced Hydrogen Production

Abstract: Coculturing dark-and photofermentative bacteria is a promising strategy for enhanced hydrogen (H 2 ) production. In this study, next-generation sequencing was used to query the global transcriptomic responses of an artificial coculture of Clostridium cellulovorans 743B and Rhodopseudomonas palustris CGA009. By analyzing differentially regulated gene expression, we showed that, consistent with the physiological observations of enhanced H 2 production and cellulose degradation, the nitrogen fixation genes in R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 71 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…From each of the two biological replicates of each culture at each time point, one 12-ml sample was collected for DNA extraction and one for RNA extraction. DNA extraction (39) and total RNA extraction, removal of genomic DNA, RNA quality assessment, and complementary DNA (cDNA) synthesis (40, 51) were carried out as described previously. Briefly, DNA was extracted using the PowerSoil DNA isolation kit (MO BIO Laboratories, USA) with minor modifications, while total RNA was extracted using the RNeasy minikit (Qiagen, USA) following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…From each of the two biological replicates of each culture at each time point, one 12-ml sample was collected for DNA extraction and one for RNA extraction. DNA extraction (39) and total RNA extraction, removal of genomic DNA, RNA quality assessment, and complementary DNA (cDNA) synthesis (40, 51) were carried out as described previously. Briefly, DNA was extracted using the PowerSoil DNA isolation kit (MO BIO Laboratories, USA) with minor modifications, while total RNA was extracted using the RNeasy minikit (Qiagen, USA) following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Culturing, analytical measurements, sample collection, and genomic DNA extraction were performed as previously described [ 24 ]. RNA extraction, removal of genomic DNA, RNA quality assessment, and cDNA synthesis were performed as previously described [ 26 ]. DNA or RNA was extracted from each of the biological replicate cultures and then pooled by equal mass into a single sample for sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In previous study, we found that the PSB06 had good effect on controlling various rice diseases. The R. palustris CGA009 (ATCC BAA-98), was obtained from the American Type Culture Collection (ACTT, USA), a different physiological subspecies of the R. palustris , which is mainly used in hydrogen production research internationally at present studies (Piskorska et al 2013; Lu et al 2016). In this study, we also explored the effects agent R. palustris CGA009 on rice growth and rhizosphere microorganisms.…”
Section: Introductionmentioning
confidence: 99%